Spezialisierte Ambulante Palliativ-Versorgung - Nauck, Friedemann; Jansky, Maximiliane (DMW - Deutsche Medizinische Wochenschrift, 2018)
Since 2007, patients with severe advanced life-limiting illnesses and high, complex symptom burdens have a right to receive specialized outpatient palliative care (SAPV). Multi-professional teams with heterogeneous organizational structures provide care in cooperation with primary care givers, not limited to cancer patients. The aim of SAPV is to foster patient’s autonomy and quality of life. SAPV can be provided as counseling of patient and care givers, coordination of care, additional supportive and full care provision. While the basis of SAPV provision is regulated by a SAPV directive, different contracts between care providers and health care insurances regulate organization, cooperation, definition of care levels, service provision and compensation. Some regions have model contracts that are binding for all SAPV teams in the area; in other regions teams negotiate e. g. compensation, individually with insurances. The article gives an overview of the regulations regarding SAPV.
Keywords: Palliativversorgung; ambulante Versorgung; Gesundheitssystem